A comparison of the performance of commercially available chromogenic agars for the isolation and presumptive identification of organisms from urine. Issue 8 (30th July 2003) - Fallon, D; Ackland, G; Andrews, N; Frodsham, D; Howe, S; Howells, K; Nye, K J; Warren, R E
Abstract : Aims: To compare four media—UTI medium, BBL CHROMagar, CPS ID2, and Harlequin CLED—using a collection of fully characterised organisms and subsequent "field trial". Methods: Seven hundred and eighty seven fully characterised isolates (730 Gram negative bacteria, 47 Gram positive bacteria, and 10 yeasts) were used to test for accuracy of organism identification. To assess isolation rates and ability to detect mixed cultures, 1435 urine samples were cultured in the three best performing chromogenic media (UTI medium, BBL CHROMagar, and CPS ID2) and CLED. Results: The chromogenic agars differed in their accuracy of identification, with BBL CHROMagar performing best and Harlequin CLED performing least well. Similarly, BBL CHROMagar achieved a higher overall isolation rate than UTI medium and CPS ID2. When mixed growth was defined as greater than two organism types, BBL CHROMagar detected more mixed cultures than did UTI medium and CPS ID2, although the differences were not significant. When mixed growth was defined as greater than one organism type the increased number of mixed growths detected by BBL CHROMagar became significant, largely because of differences in enterococcal isolation rates. Conclusion: The use of BBL CHROMagar, UTI medium, or CPS ID2 chromogenic agar as a replacement for CLED agar would improve the detection rate of contaminated urine samples. Enhanced identification helps to distinguish different species, facilitating the monitoring of bacterial resistance in support of the national antibiotic strategy. BBL CHROMagar gave the highest overall organism recovery rates, greatest ability to detect mixed cultures, and the most accurate identification of organisms.